(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This research aims to examine and analyze the influence of price and product quality on the purchasing decision of Le Minerale branded Bottled Drinking Water (AMDK) products. This research is conducted because there are still many questions regarding consumer decisions in purchasing Le Minerale products. The study samples data from 100 respondents through a survey using Google Forms with the criteria that respondents have previously purchased and consumed Le Minerale products. Data testing techniques used to examine the survey results in this study include validity testing, reliability testing, normality testing, multicollinearity testing, and heteroskedasticity testing. The research model used is a multiple linear regression model. Based on the test results, it can be concluded that price and product quality have a significant and positive influence on the purchasing decision of Le Minerale products. The findings of this research imply that PT. Tirta Fresindo Jaya should always pay attention to and improve the quality of its products to attract more consumers to purchase Le Minerale products. PT. Tirta Fresindo Jaya should also consider competitive pricing that matches the quality of its products to maintain or even increase product sales.